Communicative potential of complex sentences with compliance subordinate in Ukrainian prose of the late 20th – early 21st century (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with identification of the communicative potential of complex sentences with compliance subordinate which functionate as an independent syntactic unit and as part of a multi-component syntactic structure. The author determines that the syntactical organization of the appropriate form of verbal communication is conditioned by its purpose, functions, and communicative intent of the writer.
Keywords: complex sentence with a compliance subordinate; structural and grammatical types; elementary structure sentences; multi-component syntactic structures; intrapersonal (inner) communication; interpersonal communication; communicative potential